Formalin Versus Bouin Solution for Testis Biopsies: Which Is the Better Fixative? - James L Ellenburg; Peter Kolettis; Joseph C Drwiega; Anna M Posey; Matthew Goldberg; Mitra Mehrad; Giovanna Giannico; Jennifer Gordetsky (SAGE Publishing, 2020)
Purpose: Some resources recommended Bouin solution for the fixation of testis biopsy specimens. We compared the histologic quality of rat testicular tissue using buffered formalin and Bouin solution as fixatives. Methods: We prospectively compared the histologic quality of rat testicular tissue fixed in Bouin solution versus formalin. Testicular tissue was harvested post-mortem from six rats. Each testis was removed and sectioned in half; one half was fixed in formalin and one half in Bouin solution. Testicular tissue histology (nuclear membrane detail, nuclear granularity, cytoplasmic granularity, cytoplasmic membrane detail, and basement membrane detail) was graded as high quality (2) or low quality (1). Sloughing of cells into the lumens of the seminiferous tubules was graded on a 0-3 scale (0=none, 1=mild, 2=moderate, 3=extensive). Results: All slides regardless of fixative were of appropriate quality for the histologic evaluation of spermatogenesis. The average sloughing score for formalin cases was 1.4 and for Bouin cases 1.6. Formalin fixed tissue was found to have high quality nuclear membrane detail (2), nuclear granularity (1.9), and basement membrane detail (2). Cytoplasmic granularity was of lesser but adequate quality (1.4). Cytoplasmic membrane detail was poor, (1). Tissue fixed with Bouin solution had high quality basement membrane detail (2) and adequate cytoplasmic granularity (1.5), nuclear membrane detail (1.3) and nuclear granularity (1.4). Cytoplasmic membrane detail was poor (1). Conclusion: Compared to Bouin solution, formalin fixation of rat testicular tissue produced adequate histology for the evaluation of spermatogenesis and may be superior to Bouin solution for certain cytologic features.